Propiedades psicométricas del cuestionario Función Reflexiva Parental (PRFQ) en la población monteriana. / Psychometric properties of the Parental Functioning Questionnaire (PRFQ) in Monteria population - RUEDA MORA, Ricardo Camilo; VINACCIA ALPI, Stefano; CORREA GRISALEZ, Leidy Vanessa (Utopía y Praxis Latinoamericana, 2020)
RESUMEN La presente investigación buscó analizar la estructura factorial y la consistencia interna del Cuestionario de Función Reflexiva Parental (PRFQ) en 192 madres de hijos de 0-5 años de la ciudad de Montería, Colombia. Se Aplicó el Cuestionario de Funcionamiento Reflexivo Parental (PRFQ). El PRFQ muestra las tres dimensiones de la prueba original y un alfa de Cronbach de .81. Se sugiere eliminar un ítem para mejorar la confiabilidad y la concordancia en el cuestionario con respecto a la versión original. El Cuestionario PRFQ es válido y confiable en madres de hijos de cero a cinco años de la población monteriana. ABSTRACT The aim of the study was to analyze the factorial structure as well as the internal consistency of the Parental Reflective Functioning Questionnaire (PRFQ) in 192 mothers with children of 0-5 years old from the city of Monteria, Colombia. The PRFQ shows three dimensions of the original test and a Cronbach’s alpha of .81. It is suggested that an item be removed to improve reliability and concordance in the questionnaire with the original English version. The PRFQ is valid and reliable to be applied in mothers with children between zero and five years of age in the Monteria population.